Spectators to Facets in Colon Classification - Gopinath, M. A. (Journal of Information and Knowledge, 1985)
Presents a set of typology of characteristics for Speciators to various facets namely Basic facet, Personality facet, Property facet, Energy facet, Space facet and Time facet for use in the construction of coextensive class numbers according to Colon Classification. The application of typology Is. illustrated with examples from depth schedules for different fields of knowledge.